Image Hiding in an Audio File Using Chaotic Method via Genetic Algorithm - Kadim, Azhar (Al-Nahrain Journal of Science, 2023)
Information security is one of the most important parts of information technology and communication in the modern world. Information security has gained a lot of attention recently due to the need to transmit information through global communication channels and through the Internet. In this research, the genetic algorithm is used to develop the chaotic maps that are randomly generated by the chaotic system to find the best map by which the locations of image data are inferred to be hidden in the audio. An average image size of 64×64 pixels is used to be hidden in an audio recording of 7 seconds duration at average resolution specifications. The results show that one of the chaotic maps created at the 739 generations is the best in determining image byte hiding locations in the high-frequency band of the audio. The quality measures show the cover audio that includes the hidden image is not much different from the original input one. This confirms the validity of the proposed method and the good selection of hiding locations in accordance with information security concepts.